Epigenetic Vulnerability of Insulator CTCF Motifs at Parkinson’s Disease-Associated Genes in Response to Neurotoxicant Rotenone - Freeman, Dana M.; Wang, Zhibin (Frontiers in Genetics, 2020)
CCCTC-binding factor (CTCF) is a regulatory protein that binds DNA to control spatial organization and transcription. The sequence-specific binding of CTCF is variable and is impacted by nearby epigenetic patterns. It has been demonstrated that non-coding genetic variants cluster with CTCF sites in topological associating domains and thus can affect CTCF activity on gene expression. Therefore, environmental factors that alter epigenetic patterns at CTCF binding sites may dictate the interaction of non-coding genetic variants with regulatory proteins. To test this mechanism, we treated human cell line HEK293 with rotenone for 24 h and characterized its effect on global epigenetic patterns specifically at regulatory regions of Parkinson’s disease (PD) risk loci. We used RNA sequencing to examine changes in global transcription and identified over 2000 differentially expressed genes (DEGs, >1.5-fold change, FDR < 0.05). Among these DEGs, 13 were identified as PD-associated genes according to Genome-wide association studies meta-data. We focused on eight genes that have non-coding risk variants and a prominent CTCF binding site. We analyzed methylation of a total of 165 CGs surrounding CTCF binding sites and detected differential methylation (|>1%|, q < 0.05) in 45 CGs at 7 PD-associated genes. Of these 45 CGs, 47% were hypomethylated and 53% were hypermethylated. Interestingly, 5 out of the 7 genes had correlated gene upregulation with CG hypermethylation at CTCF and gene downregulation with CG hypomethylation at CTCF. We also investigated active H3K27ac surrounding the same CTCF binding sites within these seven genes. We observed a significant increase in H3K27ac in four genes (FDR < 0.05). Three genes (PARK2, GPRIN3, FER) showed increased CTCF binding in response to rotenone. Our data indicate that rotenone alters regulatory regions of PD-associated genes through changes in epigenetic patterns, and these changes impact high-order chromatin organization to increase the influence of non-coding variants on genome integrity and cellular survival.